Directorate General of Taxes propaganda strategy to build public trust - Darpito, Muhammad Harjuno; Winata, Winata; Kusnarno, E. Tarwo (Educoretax, 2024)
Various corruption cases involving tax officials have eroded public trust in the Directorate General of Taxes. This can be seen from a survey conducted by political indicators in April 2023 which showed that public trust in the Directorate General of Taxes was only 53.7 percent in terms of tax management. This research examines the propaganda strategy of the Directorate General of Taxes in an effort to build public trust. The theory used in this research is Arthur F. Lykke, Jr.'s strategy theory. The research method uses a qualitative design with data collection techniques through interviews and literature studies. The results showed that the Directorate General of Taxes' strategy in building public trust uses human resources and social media (means) to conduct propaganda through Instagram, by prioritizing crisis management on social media (ways) with the aim of building public trust in the Directorate General of Taxes (ends). The Directorate General of Taxes' strategy in building public trust is a combination of using the resources of 44,787 personnel spread throughout Indonesia with the support of increasing social media followers applying the concept of Employee Advocacy and supported by Tax Volunteers for the Country (Renjani) to conduct propaganda through Instagram with the aim of building public trust has succeeded in restoring public trust in the Directorate General of Taxes, this can be seen from the political indicator survey in July 2023 which shows that public trust in the Directorate General of Taxes rose to 83.7 percent in terms of tax management.